All Brexiteers now? Brexit, the Conservatives and party change. Issue 1 (April 2018) - Lynch, Philip; Whitaker, Richard
Abstract The 2016 referendum vote to leave the European Union (EU) brought about significant change in the policy and strategy of the Conservative Party. Despite David Cameron's resignation, these dramatic shifts have not been matched by changes in personnel or dominant faction as MPs who voted Remain continue to outnumber those who voted Leave at the top echelons of the party. 140 Conservative MPs, many with a record of rebellion on EU issues, voted Leave, but among Remain-voting MPs were many 'reluctant Remainers'. All except Ken Clarke subsequently voted for the Bill triggering Article 50 but, in a party long divided over the EU issue, the institutional support mechanisms underpinning policy change are fragile. Conservative divisions have also changed as soft and hard Brexiteers disagree over the withdrawal process and the UK's future relationship with the EU. With the Conservatives now a minority government, parliament offers various ways in which MPs can register dissent and influence policy, from amending core Brexit legislation to supporting critical Select Committee reports.